Lymphovascular invasion can be better than pathologic complete response to predict prognosis in breast cancer treated with neoadjuvant chemotherapy. Issue 30 (July 2018) - Ryu, Young Jae; Kang, Shin Jae; Cho, Jin Seong; Yoon, Jung Han; Park, Min Ho
Abstract : Abstract: Lymphovascular invasion (LVI) has been a predictor of worse survival outcomes in breast cancer. However, the role of LVI compared than pathologic complete response (pCR) following neoadjuvant chemotherapy (NAC) remains unclear. The aim of this study was to examine the association between LVI and survival outcomes and clinicopathological features in patients with breast cancer treated with NAC. We retrospectively analyzed 187 patients with breast cancer treated with NAC and surgery between 2005 and 2013 in our institution. Kaplan–Meier analyses were used to assess recurrence-free survival (RFS) and overall survival (OS). Median follow-up was 57.9 months. Mastectomy (vs breast conserving surgery [BCS]; hazard ratio [HR], 1.791; 95% confidence interval [CI], 1.022–3.139; P = .042), ypN1-3 stage (vs ypN0 stage; HR, 2.561; 95% CI, 1.247–5.261; P = .010), and LVI (vs no LVI; HR, 2.041; 95% CI, 1.170–3.562; P = .012) were associated with worse RFS. Mastectomy (vs BCS; HR, 2.768; 95% CI, 1.173–6.535; P = .020), LVI (vs no LVI; HR, 3.474; 95% CI, 1.646–7.332, P = .001), and human epidermal growth factor receptor 2 overexpression type (vs luminal A type; HR, 11.360; 95% CI, 1.501–85.972; P = .019) were associated with worse OS. Patients with LVI and hormone receptor-negative cancer had the worst RFS ( P < .001) and OS ( P < .001). LVI more than pCR in surgical breast cancer specimens obtained after NAC was a significant independent prognostic factor. Patients with hormonal receptor-negative cancer and LVI had unfavorable survival outcomes. We suggest that patients with hormone receptor-negative cancer and LVI should receive short-term follow-up and appropriate management.